Coordinated Epigenetic Regulation in Plants: A Potent Managerial Tool to Conquer Biotic Stress - Huang, Chien-Yu; Jin, Hailing (Frontiers in Plant Science, 2022)
Plants have evolved variable phenotypic plasticity to counteract different pathogens and pests during immobile life. Microbial infection invokes multiple layers of host immune responses, and plant gene expression is swiftly and precisely reprogramed at both the transcriptional level and post-transcriptional level. Recently, the importance of epigenetic regulation in response to biotic stresses has been recognized. Changes in DNA methylation, histone modification, and chromatin structures have been observed after microbial infection. In addition, epigenetic modifications may be preserved as transgenerational memories to allow the progeny to better adapt to similar environments. Epigenetic regulation involves various regulatory components, including non-coding small RNAs, DNA methylation, histone modification, and chromatin remodelers. The crosstalk between these components allows precise fine-tuning of gene expression, giving plants the capability to fight infections and tolerant drastic environmental changes in nature. Fully unraveling epigenetic regulatory mechanisms could aid in the development of more efficient and eco-friendly strategies for crop protection in agricultural systems. In this review, we discuss the recent advances on the roles of epigenetic regulation in plant biotic stress responses.